Pengaruh Kondisi Penyimpanan Terhadap Setting Time Bahan Cetak Alginat - Deviyanti Pratiwi; Citra Puspandari Handayaningrum (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: The normal setting of alginate impression materials will reach setting time in about 2 to 4½ minutes.The setting time will affect the length of treatment in dental treatment. The aims of this study is to identify the influence of storage condition such as temperature and air humidity on the setting time of alginate impression materials. Materials and Methods: This study was an experimental laboratory. Nine testing groups of alginate impression materials were repacked into plastic with sealed closed containers and plastic without sealed open containers stored in refrigerator (temperature 7o C) and room (temperature 28o C) for 3 and 5 weeks. The setting time was measured for each group using penetrometer Results: The results of one-way ANOVA statistical analysis (p<0.05) and post hoc LSD (p<0.05) data showed significant differences in setting time for each storage condition. Setting time of alginate impression materials without sealed in temperature 28oC for 5 weeks was faster than other storage condition. Conclusion: Contamination of air humidity and changes in temperature affect the setting time of alginate impressions tested in this study.